Rooftop and natural springs water harvesting for promotion of vegetable cultivation in drought prone Morni Hills of Haryana State - GREWAL, S. S. (Journal of Soil and Water Conservation, 2019)
The Shivalik hill region of Haryana faces acute shortage of water limiting scope of high value vegetable crops in spite of good rainfall and favorable climate. The natural spring water (SW) tapping and roof rainwater (RW) harvesting was not attempted earlier for drought proofing and hence attempted in this study. Seven brick masonry water storage tanks for (SW) and eight for roof water (RW) harvesting were constructed @Rs 1.2 lakh each including accessories having 6mx4mx1.8m size. The economic gains by the cultivation of vegetable crops with supplemental irrigation were analyzed for three samples of SW harvesting and five for RW harvesting. In case of SW harvesting, the traditional maize-mustard sequence generated net saving of Rs. 9,900/- but net gain over the traditional crops was Rs. 47,800, Rs. 51,000 and Rs. 1,38,000/acre/yr by the first, second and third beneficiary farmer, respectively. In case of RW harvesting, water of five tanks was shared by seventeen farmers. The area under tomato increased from 8 to 12.2, cucumber from 2.6 to 4.7 acres and new crops of chilies and coriander were introduced over 2.1 and 1.47 acres. The total increase in gross and net income from five tanks was Rs. 14.86 and Rs. 5.94 lakh/yr over control. The aim of crop diversification, more crops per drop or doubling the income of farmers was realized by this initiative having good scope of replication.